The changing structure of capital mobility in Singapore foreign investment inflow and outflow - Loh, Chay Hiah (2015)
The objective of this project is to explore the changing structure of capital mobility in Singapore and the rationales for the changing structure. The motivation behind this project is to provide an insight into why Singapore needs to encourage outward investment while she still needs foreign investment. Singapore has always pursued an open and receptive policy towards attracting foreign direct investment (FDI) for her economic growth. In the 1960s, Singapore needed FDI to promote industrialisation and to solve unemployment problem. In the 1970s, emphasis shifted towards attracting FDI into the capital intensive and higher value-added industries. By 1980, the economy was restructured towards export-oriented capital, knowledge and technology intensive activities. This trend is expected to continue into 1990s. The success of Singapore in attracting FDI was attributed to the presence of her political stability, attractive investment incentives, a well developed fnfrastructure, a pool of efficient and effective skilled labour as well as harmonious labour-management relations. In the 1980s, Singapore began to encourage the development of an external economy. This is due to the need to maintain rapid economic growth and the realisation that her absorptive capacity for labour intensive industry had reached her limits. Outward direct investment (ODI) also serves to complement her domestic economy. Incentives and assistance schemes were formulated to encourage ODI. Majority of the ODI is in AsiaPacific region with emphasis on labour intensive industry and financial and service sectors. A corresponding study on the FDI and ODI of the other 3 Newly Industrialising Economies (NIEs) was done. It was observed that all the 4 NIEs experienced similar upward trend in FDI and ODI.